Evaluation of the Implementation of the Field Work Practice Program - Muh. Nasrullah; Nur Anisa; Sitti Hardiyanti Arhas (Journal of Social Science and Economics (JOSSE), 2024)
School is the first and main step in developing the talents and skills possessed by everyone.  This study aims to determine the management and implementation of the field work practice program at SMKN 1 Selayar with the type of qualitative research and data collection techniques through interviews and documentation. Based on the results of this study, it is shown that the evaluation of the management and implementation of the field work practice program at SMKN 1 Selayar can be seen from the indicators of preparation, demonstration, imitation, practice, and evaluation in the "effective" category. It can be seen from the aspect of preparation that holds socialization and core meetings between teachers and parents of students to set the goals and direction of the street vendor program and conduct exploration to several agencies relevant to the existing department and the signing of the MoU. Demonstration where each department head and productive teacher provides examples of work activities that must be mastered by students during the street vendor program in the agency. Imitation provides an opportunity for students to simulate work activities that have been taught previously by utilizing the available school facilities. Practice emphasizes the responsibility of students to professionally carry out work activities in the agency by applying the knowledge and work skills that have been obtained at school and according to the direction of the field supervisor. The evaluation, which is carried out periodically every two months in the step of monitoring and identifying obstacles that may arise, and for the final assessment is the responsibility of the field supervisor to provide grades and certificates for the implementation of street vendors. These stages show that the structured commitment to achieve the objectives of the field work practice program is as stipulated in the desired regulation of the Minister of Education and Culture of the Republic of Indonesia.